Luteolin Orchestrates Porcine Oocyte Meiotic Progression by Maintaining Organelle Dynamics Under Oxidative Stress - Park, Soo-Hyun; Jeong, Pil-Soo; Joo, Ye Eun; Kang, Hyo-Gu; Kim, Min Ju; Lee, Sanghoon; Song, Bong-Seok; Kim, Sun-Uk; Cho, Seong-Keun; Sim, Bo-Woong (Frontiers in Cell and Developmental Biology, 2021)
Increasing evidence has demonstrated that oxidative stress impairs oocyte maturation, but the underlying mechanisms remain largely unknown. Here, for the first time, we examined the antioxidant role of luteolin in meiotic progression and the underlying mechanisms. Supplementation of 5 μM luteolin increased the rates of first polar body extrusion and blastocyst formation after parthenogenetic activation, and the expression levels of oocyte competence (BMP15, GDF9)-, mitogen-activated protein kinase (MOS)-, and maturation promoting factor (CDK1, Cyclin B)-related genes were also improved. Luteolin supplementation decreased intracellular reactive oxygen species levels and increased the expression levels of oxidative stress-related genes (SOD1, SOD2, CAT). Interestingly, luteolin alleviated defects in cell organelles, including actin filaments, the spindle, mitochondria, the endoplasmic reticulum, and cortical granules, caused by H2O2 exposure. Moreover, luteolin significantly improved the developmental competence of in vitro-fertilized embryos in terms of the cleavage rate, blastocyst formation rate, cell number, cellular survival rate, and gene expression and markedly restored the competencies decreased by H2O2 treatment. These findings revealed that luteolin supplementation during in vitro maturation improves porcine meiotic progression and subsequent embryonic development by protecting various organelle dynamics against oxidative stress, potentially increasing our understanding of the underlying mechanisms governing the relationship between oxidative stress and the meiotic events required for successful oocyte maturation.